Terminologisamarbete kring invandrarspråk inom kontakttolkning i Finland - Syrjänen, Satu; Eskeland, Tuula; Lund, Christine (LexicoNordica, 1999)
In 1998 the community interpretation agencies in Finland decided to work together in terminological matters. Lingua Nordica Oy arranged a workshop for interpreters in Arabic, Somalian, Kurdish, Persian and Russian. The aim of this workshop was to create equivalents for the terminology introduced in the new law of integration of immigrants. The terminology included a few neologisms and new derived words. As for the results, the workshop succeeded in putting together termlists consisting of 37 terms in five languages: Arabic, Somalian, Kurdish, Persian and Russian. The term-lists will be handed out to all community interpretation agencies in Finland to help the interpreters and translators in their work.